2016
DOI: 10.1007/s41348-016-0021-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Apple mosaic virus isolates detected in hazelnut in Poland

Abstract: Apple mosaic virus (ApMV) infects over 65 plants species of Rosaceae family including hazelnut. The virus causes chlorotic or yellow patterns, rings and mosaic symptoms on the leaves and losses in yield of nuts. The occurrence and genetic diversity of ApMV were evaluated in 14 plantations of hazelnut in Poland. A total of 13 of 125 hazelnut samples tested positive for ApMV using ELISA and reverse transcriptase-polymerase chain reaction. Several primer pairs were used for RT-PCR to amplify the coat protein (CP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…A recent phylogenetic study by Grimová, Winkowska, Ryšánek, Svoboda, and Petrzik [ 17 ] of ApMV isolates identified two major phylo-groups that were also observed by later studies [ 18 ]. In this study, these two phylo-groups were also observed, corresponding to phylo-groups 1 and 2, and a third phylo-group was also observed, consisting of recently published ApMV isolates from hazelnut that were not used in the earlier studies [ 40 ]. This study used representative sequences of phylogenetic clusters and sub-clusters from all these studies that had phylogenetically informative sites ensuring our study is the most current and inclusive analysis of ApMV RNA3 genetic diversity.…”
Section: Discussionsupporting
confidence: 66%
“…A recent phylogenetic study by Grimová, Winkowska, Ryšánek, Svoboda, and Petrzik [ 17 ] of ApMV isolates identified two major phylo-groups that were also observed by later studies [ 18 ]. In this study, these two phylo-groups were also observed, corresponding to phylo-groups 1 and 2, and a third phylo-group was also observed, consisting of recently published ApMV isolates from hazelnut that were not used in the earlier studies [ 40 ]. This study used representative sequences of phylogenetic clusters and sub-clusters from all these studies that had phylogenetically informative sites ensuring our study is the most current and inclusive analysis of ApMV RNA3 genetic diversity.…”
Section: Discussionsupporting
confidence: 66%
“…ApMV has also been studied quite well in Turkey, and some isolates have been sequenced. However, sequences of hazelnut isolate, which was reported to be genetically divergent [ 6 ], are not yet available. Therefore, hazelnut and apple isolates from Ordu and Ankara provinces obtained in this study were partially sequenced and then studied to know their molecular characters.…”
Section: Discussionmentioning
confidence: 99%
“…There was no strong agreement on ApMV phylogeny as most of the phylogenetic trees of the virus were constructed using the Neighbor-joining (NJ) method [ 2 , 5 , 6 , 18 ], while at least one applied Maximum-likelihood [ 17 ]. Thus, these proposed trees sometimes produced rather distinctive branches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some hazelnut cultivars the virus causes the reduction of both nut size and yield ( Kobylko et al, 2005 ). Yield losses can reach 42% and are associated with leaf symptoms such as chlorotic or yellow areas, rings, and mosaic patterns ( Cieślińska and Valasevich, 2016 ). In the cultivar Negret healthy trees yielded 77% higher than the infected ones ( Aramburu and Rovira, 1998 ).…”
Section: Introductionmentioning
confidence: 99%